Creation Skills of Perspective Effect Drawing of Garden Landscape Based on CAD Technology - Haixia Zheng; Jin He (Advances in Multimedia)
In order to enable more garden landscape design enthusiasts to master the creation skills of perspective renderings, this article introduces CAD computer-aided technology in the creation process of perspective renderings of garden landscapes. In the research, through case analysis, the CAD technology is compared with the commonly used sketch master SketchUp, and the detailed steps of making the garden landscape perspective renderings for small-scale modeling of garden landscapes are compared in detail. Finally, an example analysis shows that the application of CAD technology to the creation of perspective renderings of garden landscape can make the creation process more scientific, reasonable, and more ornamental.